Clinical variability of respiratory pulmonary hypertension: implications for diagnosis and management - Casali, Lucio; Carratù, Pierluigi; Sofia, Matteo (Multidisciplinary Respiratory Medicine, 2013)
Pulmonary Hypertension (PH) associated to chronic respiratory diseases is currently classified in the 3rd group, as a mild to moderate form of pre-capillary PH that progressively complicates the prognosis of associated pulmonary disease. In clinical practice, however, some unresolved issues in the respiratory PH should be considered: 1) the PH heterogeneity in some respiratory diseases, such as Chronic Obstructive Pulmonary Disease (COPD), where the prevalence of unrecognized left heart disease, or chronic pulmonary thromboembolism may change the clinical classification; 2) the combining form of severe PH which often is not correlated to chronic ventilator impairment, while outcome is strictly related to pulmonary haemodynamics. The recognition of out of proportion respiratory PH in several chronic respiratory diseases which include COPD, Idiopathic Pulmonary Fibrosis (IPF), Combined Pulmonary Fibrosis and Emphysema, Obstructive Sleep Apnea (OSA), Obesity Hypoventilation Syndrome (OHS) may be important for a comprehensive clinical classification of severe respiratory PH, as well as, for the inclusion of these patients in randomized clinical trials on PH targeted therapy.